Statine als Therapie bei Lebererkrankungen? - Sauerbruch, Tilman; Schierwagen, Robert; Trebicka, Jonel (DMW - Deutsche Medizinische Wochenschrift, 2017)
Statins have proven effects in the primary and secondary prevention of coronary disease. Besides lowering LDL-cholesterol beneficial pleiotropic consequences of statin therapy are increasingly discussed. Retrospective analyses of large cohort studies have shown favorable effects on the sequels of chronic viral induced liver disease and of non alcoholic fatty liver disease. These findings are substantiated by experimental work showing that statins reduce inflammation, fibrosis and proliferation in the diseased liver. Prospective controlled trials are necessary to elucidate whether, when and where statins have a role in the therapeutic armamentarium for liver disease.
Keywords: Statine; chronische Lebererkrankungen; Leberzirrhose; Therapie